Computed Tomographic Features in a Case of Bilateral Neoplastic Cryptorchidism with Suspected Torsion in a Dog - Stokowski, Scott; Ruth, Jeffrey; Lanz, Otto; Ziglioli, Vincent (Frontiers in Veterinary Science, 2016)
An 11-year-old male German Shepherd dog presented for inappetence and weight loss. Physical examination and initial bloodwork revealed palpable abdominal masses, mild non-regenerative anemia and thrombocytopenia. Survey radiography and abdominal ultrasonography confirmed the presence of bilateral abdominal masses and lymphadenopathy. Contrast-enhanced computed tomography (CT) was performed in order to further investigate the origin of the intraabdominal masses, confirming two enlarged cryptorchid testes, one of which had an associated CT “whirl sign”. Histopathology of the testes and lymph nodes revealed bilateral malignant Sertoli cell tumors and seminomas with lymph node metastasis of both neoplasms. The purpose of this case report is to discuss the benefits of CT in the diagnosis of cryptorchid testes and describe an additional organ that may display CT “whirl sign”.